The Relationship between Socialization in Families with Early Childhood Social Development - Rina Bastian; Syuraini Syuraini; Ismaniar Ismaniar (Universitas Negeri Padang, 2019)
The development of a child’s social in Nagari Koto Lamo Kapur IX District of Lima Puluh Kota Regency is still low. This is assumed because the socialization in the family carried out by the parents is still less effective. This purpose research to see describe the socialization in the family and the development of a child’s social. This research is that by using area random sampling technique. The data collection tool that is used is a questionnaire with data analysis of percentage calculations and using the Product Moment formula to see the relationship of both. The results based on t findings and discussion can be concluded that: (1) socialization in the family has not been done properly. (2) The social development of children is still low. (3) There is a significant relationship between socialization in the family and the social development of children. a suggestion that can be submitted is the parents need to improve the socialization in the family.Keywords: Socialization, Family, Social Development, Early Childhood